Where Fireflies Dance - Corpi, Cuento de Lucha (San Francisco, CA : Children's Book Press)
Summary: A girl and her brother spend their childhood in a small town on the Caribbean coast of Mexico.
Keywords: Brothers and sisters -- Fiction; Family life -- Fiction; Mexico -- Fiction